Towards Innovative Antibacterial Correctors for Cystic Fibrosis Targeting the Lung Microbiome with a Multifunctional Effect. (23rd June 2022) - Martina, Maria Grazia; Sannio, Filomena; Crespan, Emmanuele; Pavone, Marialaura; Simoncini, Alice; Barbieri, Francesca; Perini, Cecilia; Pesce, Emanuela; Maga, Giovanni; Pedemonte, Nicoletta; Docquier, Jean‐Denis; Radi, Marco
Abstract: Cystic fibrosis (CF) is a genetic disease caused by loss‐of‐function mutations in the CFTR gene, which codes for a defective ion channel. This causes an electrolyte imbalance and results in a spiral of negative effects on multiple organs, most notably the accumulation of thick mucus in the lungs, chronic respiratory tract infections and inflammation leading to pulmonary exacerbation and premature death. Progressive decline of lung function is mainly linked to persistent or recurring infections, mostly caused by bacteria, which require treatments with antibiotics and represent one of the major life‐limiting factors in subjects with CF. Treatment of such a complex disease require multiple drugs with a consequent therapeutic burden and complications caused by drug‐drug interactions and rapid emergence of bacterial drug resistance. We report herein our recent efforts in developing innovative multifunctional antibiotics specifically tailored to CF by a direct action on bacterial topoisomerases and a potential indirect effect on the pulmonary mucociliary clearance mediated by ΔF508‐CFTR correction. The obtained results may pave the way for the development of a simplified therapeutic approach with a single agent acting as multifunctional Antibacterial‐Corrector. Abstract : The CFTR misfolding in cystic fibrosis (CF) causes a spiral of negative effects on multiple organs, comprising accumulation of lung infections, which are the leading cause of pulmonary exacerbation. Treatment of CF requires multiple drugs with a consequent therapeutic burden and complications caused by drug‐drug interactions. Herein we report an innovative approach to target the CF lung microbiome with a multifunctional antibacterial corrector.